Flow-controlled synthesis of gold nanoparticles in a biphasic system with inline liquid–liquid separation. Issue 2 (2nd January 2020) - Chow, Edith; Raguse, Burkhard; Della Gaspera, Enrico; Barrow, Steven J.; Hong, Jungmi; Hubble, Lee J.; Chai, Roger; Cooper, James S.; Sosa Pintos, Andrea
Abstract : 4-Dimethylaminopyridine-stabilised gold nanoparticles are synthesised in a biphasic flow reactor system using organic/aqueous membrane separators and gas-permeable tubing. Abstract : We present the flow synthesis of 4-(dimethylamino)pyridine (DMAP)-stabilised gold nanoparticles in a biphasic flow reactor system. In the first stage, the reduction of gold chloride using sodium borohydride took place via gas permeable tubing to minimise pressure build-up in the lines due to hydrogen gas liberation. The use of liquid–liquid membrane separators enabled automatic washing of the intermediate tetraoctylammonium bromide (TOAB)-stabilised gold nanoparticles and for subsequent phase transfer of the organic nanoparticles to the aqueous phase using DMAP. Through a systematic investigation of DMAP concentration and ratio, the amount of DMAP necessary for full transfer of the gold nanoparticles was elucidated. This semi-automated, scalable flow process enabled the production of gold nanoparticles in high yield, with good batch-to-batch reproducibility and improved monodispersity compared to conventional batch methods.